African Pottery Roulettes Past and Present : Techniques, Identification and Distribution. - Haour, Anne (Oxbow Books, 2010)
African Pottery Roulettes Past and Present considers ethnographic, museological and archaeological approaches to pottery-decorating tools called roulettes, that is to say, short lengths of fibre or wood that are rolled over the surface of a vessel for decoration. This book sets out, for the first time, a solid typology for the classification of African pottery decorated with such tools, and forges a consensus on common methodology and standards. It gives an overview of history of research into roulette decoration in Africa and elsewhere Jomon Japan, Neolithic Europe, Siberia, and New York amon.